2016
DOI: 10.1021/acs.bioconjchem.6b00613
|View full text |Cite
|
Sign up to set email alerts
|

Light-Up “Channel Dyes” for Haloalkane-Based Protein Labeling in Vitro and in Bacterial Cells

Abstract: We describe a novel molecular strategy for engendering a strong light-up signal in fluorescence tagging of the genetically encoded HaloTag protein domain. We designed a set of haloalkane-derivatized dyes having twisted internal charge transfer (TICT) structures potentially narrow enough to partially fit into the enzyme’s haloalkane-binding channel. Testing a range of short chain lengths revealed a number of active dyes, with seven carbons yielding optimum light-up signal. The dimethylaminostilbazolium chlorohe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 25 publications
1
56
1
Order By: Relevance
“…The fluorogens were first coupled to the standard Halotag ligand reported in the literature to afford the Red‐Halo and NIR‐Halo compounds (Figure 1). Previous reports have shown that a shorter HaloTag ligand may increase the fluorogenicity through hydrophobic and cation‐π aromatic interactions or increased motion restriction [24, 29, 44] . We have thus synthesized an analogue of Red‐ Halo2 coupled to a shorter ligand chain with one ethylene glycol unit less: Red‐Halo2s (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The fluorogens were first coupled to the standard Halotag ligand reported in the literature to afford the Red‐Halo and NIR‐Halo compounds (Figure 1). Previous reports have shown that a shorter HaloTag ligand may increase the fluorogenicity through hydrophobic and cation‐π aromatic interactions or increased motion restriction [24, 29, 44] . We have thus synthesized an analogue of Red‐ Halo2 coupled to a shorter ligand chain with one ethylene glycol unit less: Red‐Halo2s (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Previous reportsh ave shownt hat as horter HaloTag ligand may increase the fluorogenicity through hydrophobic and cation-p aromatic interactions or increased motion restriction. [24,29,44] We have thus synthesized an analogue of Red-Halo2 coupled to as horter ligand chain with one ethylene glycolu nit less: Red-Halo2s ( Figure 1). We first assessed their optical properties in vitro using as tandard GST-HaloTag (GST-HT) protein ( Figure 3a nd Table S1).…”
Section: Interaction With Halotag In Vitromentioning
confidence: 99%
See 2 more Smart Citations
“…In the reported examples of fluorogenic HaloTag ligands, the dye component itself has a major non‐emissive excited state conformation which is disfavored upon ligating with the HaloTag protein to allow an emissive conformation to persist and hence to produce fluorogenicity [67] . Restricting the motion of the dye component in the binding channel of HaloTag was cited as the mechanism of fluorogenicity of the Channel Dye ( 16 in Figure 5b), [67a] while a more specific interaction with a tryptophan residue within the binding pocket has been credited with exerting a cation‐π interaction to disfavor a dark, twisted excited state and to promote a planarized emissive charge transfer state ( 17 , P9 in Figure 5b) [67c] . The Channel Dye was applied in the imaging of bacterial cells, [67a] while P9 was able to label live mammalian cells without washing steps [67c] .…”
Section: Genetically Encoded Protein/peptide Tagsmentioning
confidence: 99%